Effects of Full-Time Hospital Nurses' Work Schedules are Evaluated - ELSAYED, ATEF EID MADKOUR; alzahrani, Awatif saleem saeed; Alnajjar, najla farouq; Kariri, Nora Yahya; Alnjaar , Majdah Farooq; Hassan, Najat Abdull Aziz; ALSHAHRAN, Wejdan Talea; Kariri , Najwa Yahya; Alotaibi, Aisha Mansi; Al Sharif, Nayef Ayed Faleh; Altharmani, Sami Turki Eidhah; alsufyni, nada maqbul saleh; et al. (Journal of Ecohumanism, 2024)
Background: Nurses’ work schedules are known to impact their well-being and job performance. pandemic further intensified the workload and stress levels of hospital nurses, leading to potential changes in their work schedules and conditions. This study aimed to evaluate and compare the work schedules of full-time hospital nurses before and during the pandemic, focusing on shift patterns, working hours, and related factors. Methods: This study was conducted at a regional secondary care hospital. Work schedule data were collected from handwritten records and analyzed using IBM SPSS Statistics 26.0. The study included 24 nurses who met the inclusion criteria. Descriptive statistics, repeated measures t-tests, and independent t-tests were used to compare variables such as shift length, number of workdays, consecutive shifts, and sick leave. Statistical significance was set at p < 0.05. Results: Most nurses (75%) followed rotating shift patterns, though rotation direction was inconsistent. There was a significant increase in total annual working hours in 2024 compared to 2023. Nurses worked an average of three weekends per month, with fewer free weekends available in 2024. Sick leave usage nearly doubled in 2024, with 37.5% of nurses taking more than 10 sick days compared to 20.8% in 2023. Despite increased workload, quick returns between shifts were not observed. Conclusion: increase in nurses' working hours and sick leave usage, indicating heightened job demands and potential health impacts. The findings highlight the need for better scheduling strategies to support nurses’ well-being, including more consistent shift rotations, adequate rest periods, and policies to mitigate excessive workload during health crises.